MODEL KOMUNIKASI AYAH TERHADAP ANAK DALAM AL QURAN: KAJIAN SISTEMATIC LITERATUR REVIEW - Hikmatyar, Muhammad Ibrahim; Halimah, Fauziah Nur; Nurrohim, Ahmad (ACADEMIA: Jurnal Inovasi Riset Akademik, 2025)
ABSTRACT Every parent has a role and responsibility towards their child, especially in shaping the character and personality of the child, particularly from childhood to adolescence. The presence and involvement of both the father and mother have a significant impact on the emotional development, attitudes, and mental health of the child. If one parental figure is absent in this development, it can affect the child's ability to cope with psychological pressures and build resilience. This article examines the role of a father in establishing effective communication with his child. Through a dialogical approach to communication that is gentle and based on the values of Tawhid, the communication patterns of the father in the Quran illustrate meaningful interactions with the child. This research employs the Systematic Literature Review (SLR) method, collecting several articles that discuss the theme of the problem. The researcher then concludes the answers to the problem theme using these articles and conducts an in-depth study of various relevant literature regarding the father-child communication patterns from the perspective of the Quran and Islamic education. This study aims to explore and reflect on the values of parenting from the interactions between the father and his son, contributing to the development of modern parenting patterns that not only educate intellectually but also nurture the spirituality and holistic personality of the child. ABSTRAK Setiap orang tua memiliki peran dan tanggung jawab untuk anaknya, terkhusus dalam proses pembentukan karakter dan kepribadian anak, terutama sejak masa kanak-kanak hingga remaja. Kehadiran dan keterlibatan baik ayah maupun ibu memberikan pengaruh besar terhadap perkembangan emosional, sikap, dan kesehatan mental anak. Jika salah satu figur orang tua tidak hadir dalam perkembangan itu, akan berdampak pada kemampuan anak dalam menghadapi tekanan psikologis serta membangun ketahanan diri. Artikel mengkaji peran seorang ayah dalam menjalin komunikasi yang efektif dengan anak. Melalui pendekatan komunikasi yang dialogis, penuh kelembutan, dan berlandaskan nilai tauhid, pola komunikasi sosok ayah dalam Al Quran menunjukkan pola interaksi kepada anak dengan penuh makna yang mendalam. Penelitian ini menggunakan metode Systematic Literature Review (SLR), dengan mengumpulkan beberapa artikel yang membahas tema permasalah kemudian peneliti menyimpulkan jawaban dari tema permasalahan menggunakan artikel tersebut, dan mengkaji secara mendalam diberbagai literatur yang relevan mengenai pola komunikasi ayah-anak dalam perspektif Al-Qur’an dan pendidikan Islam. Kajian ini bertujuan untuk menggali dan merefleksikan nilai-nilai pengasuhan dari interaksi beliau bersama putranya, sebagai kontribusi terhadap pengembangan pola asuh modern yang tidak hanya mendidik secara intelektual, tetapi juga membina spiritualitas dan kepribadian anak secara holistik.